2000
DOI: 10.3386/w7466
|View full text |Cite
|
Sign up to set email alerts
|

Job Creation, Job Destruction, and the Real Exchange Rate

Abstract: This paper contributes to an understanding of internationally generated adjustment costs by demonstrating a statistically significant and economically relevant effect of the real exchange rate on job creation and job destruction in U.S. manufacturing industries over the period 1973 to 1993. The responsiveness of these gross job flows to the real exchange rate reflects pervasive heterogeneity with respect to international conditions across firms, even within narrowly defined industries. We document this heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 6 publications
7
86
1
1
Order By: Relevance
“…that job creation is more responsive to import price changes than job destruction, requires careful consideration. In one estimate of essentially the same specification based on comparable US data, Klein et al (2000) found that the responsiveness of job destruction is larger than that of job creation in the USA. The previous results from accumulated related studies suggest that greater responsiveness of job destruction has been confirmed in the US manufacturing industries, but not necessarily in other cases.…”
Section: Regressions Of Job Creation and Job Destructionmentioning
confidence: 98%
See 2 more Smart Citations
“…that job creation is more responsive to import price changes than job destruction, requires careful consideration. In one estimate of essentially the same specification based on comparable US data, Klein et al (2000) found that the responsiveness of job destruction is larger than that of job creation in the USA. The previous results from accumulated related studies suggest that greater responsiveness of job destruction has been confirmed in the US manufacturing industries, but not necessarily in other cases.…”
Section: Regressions Of Job Creation and Job Destructionmentioning
confidence: 98%
“…7 4 After eliminating all four-digit industries without one-to-one direct correspondence between domestic industry classification and tariff classification, 334 industries remained in the sample. The coverage of industries is roughly as comprehensive as that in Klein et al (2000), covering 442 four-digit industries in the USA. 5 This paper uses a gross job flow data set, covering three census years, 1988, 1990 and 1993, published by Morikawa and Tachibanaki (1997).…”
Section: Description Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with the existing literature. For example, Klein, Schuh, and Triest (2003) find that a depreciation shock in the cyclical component of the U.S. dollar exchange rate tends to decrease job destruction but has little effect on job creation, thus it increases net employment growth. This view is shared by, among others, Burgess and Knetter (1998), Goldberg and Tracy (2001); the authors document that the U.S. dollar exchange rate movement is negatively related to aggregate employment growth and nominal wages in the United States.…”
Section: Figurementioning
confidence: 99%
“…Gourinchas (1999) analyzes the effect of the exchange rate on wages and, to the best of our knowledge, is the first to use industry-specific REER in such an analysis. Subsequently, in empirical studies, Campa and Goldberg (2001) and Klein et al (2003) emphasize the importance of disaggregated REER. Goldberg (2004) uses industry-specific trade data for the USA to construct industry-specific REER for 20 different industries.…”
Section: Introductionmentioning
confidence: 99%